Computer-aided Instruction, Learning Styles and Academic Achievement: Interplay Towards Understanding of Philippine Literature for Grade 7 Students - Goroleo, Jocelyn (Journal of Research and Investigation in Education, 2024)
In the current era of education, the utilization of computer-based materials is widespread and has become more common as years pass by. The researcher aims to determine the effectiveness of teaching literature using computer-based materials as a strategy in teaching Philippine literature to Grade 7 students. This study seeks to compare the level of learning in terms of knowledge and practical skills acquisition and craftsmanship between learners using computer-based instructional materials and those using print- based instructional materials in teaching Philippine Literature. A quasi-experimental design is highly appropriate and considered to be effective for this research because it uses the pre-testing and post-testing of the respondents about the investigation at hand. Findings showed that the students always use visual (spatial) learning styles as they prefer to learn using pictures, images, and spatial understanding. In addition, the results revealed that the pupils’ performance was improved with Computer-Aided Instruction (CAI). In line with this. the participants also showed preference to different methods such as the usage of DVD Video and social networking sites like Facebook for educational purposes. However, the research also uncovered setbacks to the ease of using computer-aided instructions. According to the participants, these difficulties include the availability of hardware and software, lack of funds, computer illiteracy, and attitudes of teachers.